2012
DOI: 10.1177/039463201202500329
|View full text |Cite
|
Sign up to set email alerts
|

Impact and Oral Immunotherapy on Quality of Life in Children with Cow Milk Allergy: A Pilot Study

Abstract: Quality of life is negatively affected in children with food allergy. Oral immunotherapy is an approach to food allergy that leads to patient desensitization by administering gradually increasing amounts of a given food allergen. The aim of this pilot study is to evaluate how oral immunotherapy affects quality of life in children allergic to cow milk proteins. Thirty children (aged 3-12 years) with cow milk allergy were recruited. Their parents were provided with a validated disease specific quality oflife que… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(54 citation statements)
references
References 13 publications
1
40
1
Order By: Relevance
“…Oral immunotherapy is a promising therapy for FA. Studies in patients and parents have demonstrated a general positive effect of OIT on some aspects of QoL, especially food anxiety and social and dietary limitation but not emotional impact . Certain characteristics seem to be associated with greater improvements in caregiver QoL: in a prospective randomized study, QoL improved more in caregivers of participants older than 10 years or desensitized to more than 4 food allergens than those who were not …”
Section: Results From the Selected Literaturementioning
confidence: 99%
“…Oral immunotherapy is a promising therapy for FA. Studies in patients and parents have demonstrated a general positive effect of OIT on some aspects of QoL, especially food anxiety and social and dietary limitation but not emotional impact . Certain characteristics seem to be associated with greater improvements in caregiver QoL: in a prospective randomized study, QoL improved more in caregivers of participants older than 10 years or desensitized to more than 4 food allergens than those who were not …”
Section: Results From the Selected Literaturementioning
confidence: 99%
“…This raises the question as to whether reactions with dosing outweigh the benefit gained from therapy, which can only be addressed by an objective evaluation of quality of life influenced specifically by health and disease, or health-related quality of life (HRQL) [14-16]. While single-allergen OIT has been found to result in HRQL improvement in participants with peanut or cow milk allergy [17,18], this study is the first to investigate the effects of mOIT and of rush mOIT with omalizumab on FA-related HRQL.…”
Section: Introductionmentioning
confidence: 99%
“…Patients with a positive result to an OFC for heated cow's milk can poorly tolerate cow's milk in any form 3. Patients were forced to accept the elimination of cow's milk from their diet, thereby decreasing their QOL.…”
Section: Discussionmentioning
confidence: 99%